Sense and Sensibility - "Jane Austen" (lONDON, 1996)
Sense and Sensibility is a novel by Jane Austen that tells the story of the impoverished Dashwood family, focusing on the sisters Elinor and Marianne, personifications of good sense and sensibility, respectively12. They become destitute upon the death of their father, who leaves his home, Norland Park, to their half brother, John1.